Potensi Interaksi Obat pada Pasien Geriatri Diabetes Melitus Tipe 2 di RSUD Dr. Moewardi Surakarta Tahun 2023 - Dilla Ayu Septiyani; Adhi Wardhana Amrullah; Rolando Rahardjoputro (Asosiasi Riset Ilmu Kesehatan Indonesia, 2024)
Type 2 diabetes mellitus represents a persistent metabolic dysfunction marked by elevated blood glucose levels attributable to insulin resistance. Geriatrics pertains specifically to individuals aged 60 years and older. Managing diabetes mellitus necessitates intricate therapeutic interventions, often comprising single or combined pharmacological agents aimed at achieving euglycemia. The concurrent administration of multiple medications, termed polypharmacy, amplifies the likelihood of pharmacological interactions. This investigation endeavors to delineate potential drug interactions observed in geriatric inpatients afflicted with type 2 diabetes mellitus at Dr. Moewardi Regional General Hospital in Surakarta throughout the calendar year 2023. The study adopted a descriptive observational design employing a cross-sectional approach. Data collection was conducted retrospectively through purposive sampling based on the medical records of geriatric patients at Dr. Moewardi Regional General Hospital in Surakarta. Inclusion criteria encompassed patients aged 60 years and older diagnosed with type 2 diabetes mellitus who had been hospitalized. Exclusion criteria included incomplete or illegible medical records, patients diagnosed with anemia and hemoglobinopathies, and those who expired during treatment. The findings revealed that out of 100 patients, 96 experienced drug interactions. Most patients (47.00%) were aged between 66 and 74 years. Females constituted a larger proportion (51.00%) of the patient cohort. Among hospitalized patients, 83 (83.00%) were admitted for 2-6 days. A total of 70 patients (70.00%) were prescribed between 4 and 13 medications. The predominant severity level of drug interactions was moderate, comprising 1,017 cases (74.60%). Pharmacodynamic mechanisms accounted for most drug interactions observed, totaling 1,054 cases (77.30%).